A simulation on the transient response of a capacitor voltage transformer using MATLAB / Nursyarizal Mohd Nor and Zuhairi Baharudin - Mohd Nor, Nursyarizal; Baharudin, Zuhairi (2004)
This paper presents a study on the transient response behavior of a capacitor voltage transformer based on the simulation done using MATLAB. The adopted equivalent circuit is modeled in MATLAB using mathematical equations obtained through mathematical simplifications of the circuit. Based on this model, the effects of CVT components such as capacitor and ferroresonance suppression circuit, and the effects of fault type, point-an-wave and location on the CVT transient response are studied through observation on the MATLAB-generated transient responses. The ideal input voltage to the CVT is obtained from an ideal power transmission line system model in PSCAD/EMTDC.